The Path of Forgetting : the Microcosm in the Macrocosm. (Gabriele Publishing House, 2017)
Only the fewest people know who they are, not to mention where they come from and where they are going. Most people live their life in the illusory world of matter, as if it were the sole reality. Here, we learn how everything that we feel, think, say and do as human beings is not only continuously stored in the microcosm man, but is in constant communication with further memory sources in the coarse-material macrocosm and beyond that, in a finer-material macrocosm ...